1995
DOI: 10.1164/ajrccm.151.5.7735595
|View full text |Cite
|
Sign up to set email alerts
|

Circulating ICAM-1 is increased in septic shock.

Abstract: Adhesion molecules play a critical role in the interaction of circulating neutrophils with vascular endothelium during inflammation. Increased quantities of soluble, circulating intercellular adhesion molecule-1 (cICAM-1) are present in various inflammatory conditions. The purpose of this investigation was to measure cICAM-1 levels in septic adults, as well as to examine the relationship between this potential marker of endothelial-cell activation and the consequences of sepsis (i.e., multiple organ failure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
1
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 28 publications
8
69
1
6
Order By: Relevance
“…The highest serum concentrations of both various cytokines as well as adhesion molecules have been reported in patients with septic shock and fatal outcome [4,7,8]. In the present study nonsurvivors showed higher serum levels of all the three adhesion molecules compared with those who did survive, but the differences did not reach statistical signi®cance.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…The highest serum concentrations of both various cytokines as well as adhesion molecules have been reported in patients with septic shock and fatal outcome [4,7,8]. In the present study nonsurvivors showed higher serum levels of all the three adhesion molecules compared with those who did survive, but the differences did not reach statistical signi®cance.…”
Section: Discussioncontrasting
confidence: 72%
“…It has also been proposed that the release of E-selectin is related to the degree of vascular or endothelial injury caused by the sepsis [4]. Increased plasma and serum levels of VCAM-1 and ICAM-1 have been shown in bacteremic patients [7,8]. E-selectin as well as ICAM-1 has also been found to be associated with multiple organ dysfunction, septic shock and death [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7-9 Increased quantities of soluble circulating adhesion molecules have also been detected in various models of liver injury. 2,7,8,10 These findings, together with the observation that liver injury is abrogated by administration of antibodies to certain cell adhesion molecules, [4][5][6]11 suggest that they play a role in hepatotoxicity associated with inflammation.Endotoxin is a bacterially derived product known to induce liver injury at toxic doses. 12 We have previously demonstrated that acute endotoxemia is associated with an increase in the number of macrophages in the liver.…”
mentioning
confidence: 97%
“…Upon activation, endothelial cells and adhesion molecules are shed. The increased levels of circulating endothelial cells and adhesion molecules in septic patients may therefore reflect factors of importance to parallel changes in the capillary circulation 42, 43, 44, 45, 46…”
Section: The Origins Of Capillary Flow Disturbances or Occlusion In Smentioning
confidence: 99%